Analyzing The Determinants of Financial Distress In Indonesian Sharia Banking With ISR as a Moderating Variable - Muhammad Tamul Fikri; Rossje V Suryaputri; Yasir Arafat (Universitas Muhammadiyah Prof. DR HAMKA., 2022)
This study aims to analyze the determination of Financial Distress in Indonesian Islamic Banking with ISR as a Moderating Variable. The data used is secondary data obtained from the financial statements of Islamic Banking listed on the Indonesia Stock Exchange. This research is a research conducted by testing the hypothesis. A total of 11 samples from 14 banks with an observation period of 5 years, 2016-2020 were selected using Data Cross Sections and time series methods. The analytical method used to test the hypothesis in this study is panel data regression analysis. The results of this study indicate that the variable score of Corporate Governance has a negative effect on Financial Distress, while the Board Director, Board Syariah Director and ISR have a positive effect on Financial Distress.